A Study on the Income Tax Problem of Manufacturing Industries of Nepalgunj Industrial Estate (Voice: A Biannual & Bilingual Journal, 2025)
A tax imposed on income is called income tax. It is divided into two parts: Individual income tax and corporate income tax. The Income Tax Act of Nepal was revised eight times. It has made a significant contribution to Nepal’s economic development. According to this research, sixty per cent of the respondents believe that the Nepalese income tax system is ineffective. Only forty per cent of those present thought that it was effective. The significant problems with income tax include frequent changes to the income tax act, Corruption, a lack of systematic evaluation and control mechanisms, and others.